Efficacy of maternal tenofovir disoproxil fumarate in interrupting mother‐to‐infant transmission of hepatitis B virus. Issue 2 (13th May 2015) - Chen, Huey‐Ling; Lee, Chien‐Nan; Chang, Chin‐Hao; Ni, Yen‐Hsuan; Shyu, Ming‐Kwang; Chen, Shih‐Ming; Hu, Jen‐Jan; Lin, Hans Hsienhong; Zhao, Lu‐Lu; Mu, Shu‐Chi; Lai, Ming‐Wei; Lee, Chyi‐Long; et al.
<x xml:space="preserve">Abstract</x> The efficacy and safety of maternal tenofovir disoproxil fumarate (TDF) in reducing mother‐to‐infant hepatitis B virus (HBV) transmissions is not clearly understood. We conducted a prospective, multicenter trial and enrolled 118 hepatitis B surface antigen (HBsAg)– and hepatitis B e antigen–positive pregnant women with HBV DNA ≥7.5 log10 IU/mL. The mothers received no medication (control group, n = 56, HBV DNA 8.22 ± 0.39 log10 IU/mL) or TDF 300 mg daily (TDF group, n = 62, HBV DNA 8.18 ± 0.47 log10 IU/mL) from 30‐32 weeks of gestation until 1 month postpartum. Primary outcome was infant HBsAg at 6 months old. At delivery, the TDF group had lower maternal HBV DNA levels (4.29 ± 0.93 versus 8.10 ± 0.56 log10 IU/mL, P < 0.0001). Of the 121/123 newborns, the TDF group had lower rates of HBV DNA positivity at birth (6.15% versus 31.48%, P = 0.0003) and HBsAg positivity at 6 months old (1.54% versus 10.71%, P = 0.0481). Multivariate analysis revealed that the TDF group had lower risk (odds ratio = 0.10, P = 0.0434) and amniocentesis was associated with higher risk (odds ratio 6.82, P = 0.0220) of infant HBsAg positivity. The TDF group had less incidence of maternal alanine aminotransferase (ALT) levels above two times the upper limit of normal for ≥3 months (3.23% versus 14.29%, P = 0.0455), a lesser extent of postpartum elevations of ALT (P = 0.007), and a lower rate of ALT over five times the upper limit of normal (1.64% versus 14.29%, P = 0.0135) at 2 months postpartum. Maternal creatinine and creatinine kinase levels, rates of congenital anomaly, premature birth, and growth parameters in infants were comparable in both groups. At 12 months, one TDF‐group child newly developed HBsAg positivity, presumably due to postnatal infection and inefficient humoral responses to vaccines. Conclusions: Treatment with TDF for highly viremic mothers decreased infant HBV DNA at birth and infant HBsAg positivity at 6 months and ameliorated maternal ALT elevations. (Hepatology 2015;62:375–386